Ethnoveterinary practices in the Tena Valley and Biescas Area (Spanish Pyrenees) for the care of sheep and goats - López Marco L.; Obón C. (Innovation for sustainability in sheep and goats, 2019)
This study covers traditional healing practices for sheep and goats recorded in the Tena Valley and Biescas Area (Spanish Pyrenees). 30 informants were interviewed and 60 different plant taxa were registered belonging to 35 botanical families, as well as 7 herbal remedies, 1 fungus, 9 elements of animal origin, 9 of mine ral origin, 1 of chemical origin and 7 handling practices or other remedies. In total, 149 practices for medicinal, reproductive or production uses in small ruminants were recorded. These traditional practices are very useful for organic farming as alternatives to synthesised medicinal products and as non-conventional feeds, and contribute to maintaining traditional knowledge, which has been passed on from one generation to the next and has been falling into disuse in recent times. Therefore there is an urgent need to record knowledge related to ethnoveterinary practices to conserve them and thus enable the development of new remedies.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)